2005
DOI: 10.1063/1.1984091
|View full text |Cite
|
Sign up to set email alerts
|

Chemical reaction at the interface between polycrystalline Si electrodes and HfO2∕Si gate dielectrics by annealing in ultrahigh vacuum

Abstract: We have investigated the chemical reaction at the interface between polycrystalline-Si (poly-Si) electrodes and HfO2∕Si gate dielectrics by photoemission spectroscopy and x-ray absorption spectroscopy depending on the annealing temperature in an ultrahigh vacuum. From Si2p and Hf4f high-resolution core-level photoemission spectra, we revealed that the Hf-silicide formation starts at as low temperature as 700°C and that the Hf-silicate layer is also formed at the interface between poly-Si electrodes and HfO2. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
12
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 17 publications
0
12
1
Order By: Relevance
“…On the other hand, the ZrO 2 /Si interface was found to be unstable around 1000K, which is in contradiction to the calculation by Hubbard and Schlom [2]. It was also observed that the Hf-silicide forms upon decomposition of HfO 2 in low oxygen partial pressures [5,6,7,8] and HfSiO 4 suppresses Hf-silicide formation [9].Although the phase stabilities in the Hf-Si-O and Zr-Si-O systems are important, comprehensive thermodynamic explanations are not yet available. In this paper, based on the recently developed thermodynamic descriptions of the Hf-Si-O[10] and Zr-Si-O systems with first-principles calculations and thermodynamic CALculation of PHAse Dia- * Corresponding author.…”
contrasting
confidence: 54%
See 2 more Smart Citations
“…On the other hand, the ZrO 2 /Si interface was found to be unstable around 1000K, which is in contradiction to the calculation by Hubbard and Schlom [2]. It was also observed that the Hf-silicide forms upon decomposition of HfO 2 in low oxygen partial pressures [5,6,7,8] and HfSiO 4 suppresses Hf-silicide formation [9].Although the phase stabilities in the Hf-Si-O and Zr-Si-O systems are important, comprehensive thermodynamic explanations are not yet available. In this paper, based on the recently developed thermodynamic descriptions of the Hf-Si-O[10] and Zr-Si-O systems with first-principles calculations and thermodynamic CALculation of PHAse Dia- * Corresponding author.…”
contrasting
confidence: 54%
“…The calculated isopleths indicate that metal silicates play an important role in the silicide formation as suggested by Takahashi et al [9] From first-principles calculations, the formation enthalpy of ZrSiO 4 is −2.358 ± 1 kJ/mol-atom whereas that of HfSiO 4 is only −1.769 ± 1 kJ/mol-atom when the reference states are set to the binary oxides. It is intriguing to see that such a small (0.6 kJ/mol-atom) difference in the formation of metal silicates greatly affects the phase stability at the metal oxides/silicon interface.…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…There are two possibilities for the mechanism of the Hf silicide formation 1) Hf atoms formed during electron-beam evaporation directly react with Si, and 2) deposited HfO 2 reacts with Si. It is reported in the previous literature that in the case of HfO 2 deposition by means of reactive magnetron sputtering, Hf silicide is formed only at temperatures above 700°C [33]. This indicates that deposited HfO 2 does not react with Si at temperatures below 700°C, and thus mechanism 1) is more probable.…”
Section: Discussionmentioning
confidence: 90%
“…1͑a͒ and 1͑b͒ respectively. At T s = 500°C, only a doublet peak corresponding to the Hf-Al-O bond 16 was observed, while a new doublet peak corresponding to the Hf-Si bond 17 appeared at T s = 600°C. The peak from the Hf-Al-O bond fell with increasing T s and finally disappeared at T s = 800°C.…”
mentioning
confidence: 88%